2011
DOI: 10.1152/ajpregu.00089.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker activity in the insect (T. molitor) heart: role of the sarcoplasmic reticulum

Abstract: The electrophysiological properties of the myogenic cardiac cells of insects have been analyzed, but the mechanisms that regulate the pacemaker activity have not been elucidated yet. In mammalian pacemaker cells, different types of membrane ion channels seem to be sequentially activated, perhaps in a cooperative fashion with the current generated by Ca(2+) extrusion mediated by the electrogenic Na(+)/Ca(2+) exchanger, which is sustained by the diastolic sarcoplasmic reticulum (SR) Ca(2+) release. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 44 publications
2
26
0
16
Order By: Relevance
“…Our study demonstrated that older beetles had more abnormalities, like arrhythmia, in heart rhythm, which was constant from posterior to anterior (registered by visual observations). This regular rhythm was also observed in previous studies of T. molitor heart physiology (Feliciano, Bassani, Olivieira, & Bassani, ; Markou & Theophilidis, ). In T. molitor , the spontaneous electrical activity always originates at the most posterior cardiac segment and travels to the most anterior region of the dorsal vessel (Markou & Theophilidis, ).…”
Section: Disscussionsupporting
confidence: 87%
“…Our study demonstrated that older beetles had more abnormalities, like arrhythmia, in heart rhythm, which was constant from posterior to anterior (registered by visual observations). This regular rhythm was also observed in previous studies of T. molitor heart physiology (Feliciano, Bassani, Olivieira, & Bassani, ; Markou & Theophilidis, ). In T. molitor , the spontaneous electrical activity always originates at the most posterior cardiac segment and travels to the most anterior region of the dorsal vessel (Markou & Theophilidis, ).…”
Section: Disscussionsupporting
confidence: 87%
“…The heartbeat frequency measured in the S. exigua pupae was significantly decreased after topical application of both tested extracts. Proper functioning of the heart is one of the major physiological processes essential for normal functioning of the insect organism (Feliciano et al 2011). Even slight alterations in the heart functioning may interrupt the homeostasis and cause severe changes (Piazza & Wessells 2011).…”
Section: Disscussionmentioning
confidence: 99%
“…In insect Tenebrio molitor , a mealworm beetle, application of 5 mM 2,3‐butanedione monoxime (BDM) for 2 min significantly decreases the mechanical activity of the heart, whereas no effects on electrogram were observed (Feliciano, Bassani, Oliveira, & Bassani, ). They have used low‐impedance suction microelectrodes made of glass in contrast to a flexible small diameter plastic tube with a narrow end/opening that is fire polished to unfailingly achieve tight contacts (Kodirov, ).…”
Section: Introductionmentioning
confidence: 99%
“…They have used low‐impedance suction microelectrodes made of glass in contrast to a flexible small diameter plastic tube with a narrow end/opening that is fire polished to unfailingly achieve tight contacts (Kodirov, ). BDM almost obliterates the contraction within 10 min, but the electrical activity changes only in rate and amplitude (Feliciano et al, ). The depolarizing and repolarizing polarity distribution of electrograms also differ compared with the control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation